Predicting Financial Outcome Gaps in ICU Services for National Health Insurance Patients Based on Length of Stay Comorbidity and Outcomes - Yurisa Kinanti; Mappa Panglima Banding (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
Intensive Care Unit (ICU) services represent the most clinically complex and cost-intensive hospital units, often creating discrepancies between actual service costs and Indonesia Case-Based Groups (INA-CBGs) reimbursement, particularly for National Health Insurance (JKN) patients. These discrepancies are reflected in financial outcome gaps, which may threaten hospital financial sustainability when negative. This study analyzes the effects of length of stay (LOS), number of comorbidities, and patient outcomes on ICU financial outcome gaps and develops a regression model to predict the risk of negative financial outcomes among JKN ICU patients at RSUD dr. H. Jusuf SK. A quantitative retrospective observational design was applied using data from 290 JKN ICU patients treated between July 1, 2024, and June 30, 2025. Data were analyzed using descriptive statistics, simple linear regression, and multiple linear regression with robust standard errors (HC3) in SPSS version 27. The results indicate an average ICU LOS of 3.45 ± 3.03 days, a mean of 7.05 ± 3.67 comorbidities, and an average financial outcome gap of −IDR 23,149,588. Simple regression analysis shows that LOS, comorbidities, and patient outcomes significantly affect financial outcome gaps. Multiple regression results confirm that these variables simultaneously influence financial outcome gaps (R² = 0.217). The developed model demonstrates low-to-moderate explanatory power and may serve as an early, non-clinical predictive tool to identify financial risk and support managerial decision-making in ICU financing under the INA-CBGs system.